Training and Marketing Channel as Determinant of Empowerment of Rural Self Help Group Women Members - Kumari, Neelam; Malik, Joginder Singh; Ghalawat, Suman (Indian Journal of Extension Education, 2019)
The present study was conducted on 120 randomly selected respondents from Bhiwani and Bawani Khera blocks of Bhiwani district of Haryana state. The study revealed that majority of the respondents belonged to the young age group, illiterate, belonged to nuclear families of medium family size. Hundred per cent of the respondents were active with social participation in one organization. Training received score was obtained highest for income generation (weighted mean score 2.00 and rank I), followed by loaning and dairy and agriculture ranked II and III respectively. Similarly for marketing channels ‘individual sale mode of marketing’ ranked first, followed by ‘group contacts with shopkeeper in village/nearby village’, ‘group contacts with shopkeepers in cities’ and ‘group sale’ respectively. Association between independent variables with training and marketing channels was found positively correlated. It was interesting that a negligible percentage of respondents performed tasks of income generating activities and marketing which were not fruitful for them.
Keywords: Income generation; Marketing channel; Respondents; Self Help Groups; Training received; Women